Is Extracellular Vesicle-Based Therapy the Next Answer for Cartilage Regeneration? - Velot, Émilie; Madry, Henning; Venkatesan, Jagadeesh K.; Bianchi, Arnaud; Cucchiarini, Magali (Frontiers in Bioengineering and Biotechnology, 2021)
“Extracellular vesicles” (EVs) is a term gathering biological particles released from cells that act as messengers for cell-to-cell communication. Like cells, EVs have a membrane with a lipid bilayer but unlike these latter, they have no nucleus and consequently can’t replicate. Several EV subtypes (e.g., exosomes, microvesicles) are described in the literature. However, the remaining lack of consensus on their specific markers prevents sometimes the full knowledge of their biogenesis pathway, causing the authors to focus on their biological effects and not their origins. EV signals depend on their cargo which can be naturally sourced or altered (e.g., cell engineering). The ability for regeneration of adult articular cartilage is limited because this avascular tissue is partly made of chondrocytes with a poor proliferation rate and migration capacity. Mesenchymal stem cells (MSCs) had been extensively used for cartilage regeneration and it has been demonstrated that their therapeutic effects are due to paracrine mechanisms involving EVs. Hence, using MSC-derived EVs as cell-free therapy tools has become a new therapeutic approach to improve regenerative medicine. EV-based therapy seems to show similar cartilage regenerative potential compared to stem cell transplantation without the associated hindrances (e.g., chromosomal aberrations, immunogenicity). The aim of this short review is to take stock of occurring EV-based treatments for cartilage regeneration according to their healing effects. The manuscript focuses on cartilage regeneration through various sources used to isolate EVs (mature or stem cells among other), and beneficial effects depending on cargoes produced from natural or tuned EVs.